Antecedents of switching intention in the mobile telecommunications industry: A partial least square approach - Quoquab, Farzana (Emerald Group Publishing Ltd., 2018)
Purpose: This study sheds some light on factors that affect customer switching intention in the Malaysian mobile phone service industry. More particularly, the purpose of this paper is to examine the effect of service quality (SQ), customer satisfaction, switching cost and consumer innovativeness (CI) on service switching intention (SWI); the mediating role of customer satisfaction; and the moderating role of service switching cost on the relationship between CI and SWI. Design/methodology/approach: Data were collected using a self-administered questionnaire survey that yielded 535 responses. Using structural equation modelling approach, the partial least square software, version 3 was utilised to test the study hypotheses. Findings: Results reveal that customer satisfaction, service switching cost and CI directly affect SWI. However, no significant relationship was found between SQ and SWI. Again, data supported the mediating effect of customer satisfaction as well as the moderating effect of service switching cost. Research limitations/implications: It is expected that the findings from this study will enable policymakers, managers and marketers to formulate better strategies and effectively implement loyalty programs, preventing their customers from switching. Originality/value: This study contributes to the existing literature by testing switching costs as the quasi moderator. Moreover, this is a pioneer study to consider CI as the antecedent of SWI.